1987
DOI: 10.1159/000261015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of the Caries Inhibition of Two Mixed NaF-Na2PO3F Dentifrices Containing 1,000 and 2,500 ppm F Compared to a Conventional Na2PO3F Dentifrice Containing 1,000 ppm F: Results after Two Years

Abstract: The 2-year caries increments of fifth to seventh grade students (mean age 11.7 years) residing in two fluoride-deficient communities (F < 0.1 ppm) on Long Island, N.Y., were compared relative to their use of different fluoride dentifrices. Group I used a conventional Na2PO3F dentifrice (1,000 ppm F) and served as the positive control. Group II used a mixed fluoride dentifrice containing equimolar amounts of NaF and Na2PO3F which provided a total fluoride concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…For example, if one uses a S. mutans CFU count greater than 10\ the sensitivity and specificity are 33% and 81%, respectively; using a CFU count greater than lO'' for lactobacilli produces a sensitivity and specificity of 45% and 81%, respectively. LACTOBACILLI distribution of lactobacilli at the initial (BL) and 17-month (follow-up) DMFS (annualized) is low compared with those typically realized in US nonfiuoridated communities as recently as the late 197O's (17), but appears consistent with those currently being reported in the US (18)(19)(20). This decreased level of caries activity makes it more difficult to demonstrate associations with caries incidence, especially on an individual subject basis.…”
Section: Resuitssupporting
confidence: 71%
“…For example, if one uses a S. mutans CFU count greater than 10\ the sensitivity and specificity are 33% and 81%, respectively; using a CFU count greater than lO'' for lactobacilli produces a sensitivity and specificity of 45% and 81%, respectively. LACTOBACILLI distribution of lactobacilli at the initial (BL) and 17-month (follow-up) DMFS (annualized) is low compared with those typically realized in US nonfiuoridated communities as recently as the late 197O's (17), but appears consistent with those currently being reported in the US (18)(19)(20). This decreased level of caries activity makes it more difficult to demonstrate associations with caries incidence, especially on an individual subject basis.…”
Section: Resuitssupporting
confidence: 71%
“…Sinee the trial commenced in 1983, further reports have been published relating to toothpastes with different fluoride concentrations. In these, MITROPOULOS et al (7), DiODATi et al, (8), and TRIOL et al (9) showed significant dose-response relationships, whereas RIPA et al (10) reported no such effect.…”
mentioning
confidence: 98%
“…For several decades fluorides (F) have been avail able in toothpastes, and today almost all products used in the industrialized countries contain up to 1,000 ppm F, or even more [Forward, 1980;Stookey, 1985;Ripa et al, 1987], Ericsson and Forsman [1969] suggested that toothpastes with either sodium F (NaF) or sodium monofluorophosphate (MFP) should con tain less than 0.1% F if used by children of tooth-min eralizing ages. Since F in toothpaste is known to have a high bioavailability [Ekstrand and Ehrnebo, 1980;Ekstrand et al, 1983], the risk of an increase in dental fluorosis from too high a daily F intake should be taken into consideration [Barnhart et al, 1974;Hei fetz and Horowitz, 1984;Beltran, 1988;Bruun and Thylstrup, 1988].…”
mentioning
confidence: 99%